Social dimensions of geographic disorientation in Arctic Alaska - Sonnenfeld, Joseph (Études/Inuit/Studies, 2002)
AbstractA recent study of the wayfinding techniques employed by Inupiat residing in the communities of Barrow, Wainwright, and Anaktuvuk Pass, suggests that the incidence of disorientation episodes has increased in recent decades, despite easier access to maps and compasses and other aids to navigation and wayfinding. A general model, which focuses on the environmental and cognitive sources of disorientation, is introduced to help understand this apparent deterioration in Inupiat travel skills. Some social consequences of disorientation are also discussed, including: (a) the community reaction to individuals who get lost; and (b) resolution of spatial conflicts during group travel. Finally, questions are raised concerning the nature of "traditional knowledge," and its role in the Inupiat wayfinding system.